Exploration of Academic Stress among Undergraduates of Sukkur IBA University Through the Lens of Gender Differences - Zamir, Sharik; Akhund, Maria; Ahmed Khoso, Ikhtiar (The Journal of Humanities & Social Sciences, 2023)
Personal and institutional expectations fall onerous on students resulting in stress. During academic life, students attempt to manage stressors stemming from social, personal, academic, and environmental fronts. Almost every day, students experience academic stress in their university life. This scenario necessitates for this study to explore undergrads academic stress, compare and analyze the differences of academic stress among males and females, in a public sector university. The positivist paradigm applied as the worldview, and quantitative research as a method of inquiry. The sample comprised of 99 (70 males and 29 female) undergrads selected on voluntary-participation criterion, who were enrolled across eight semesters. The student academic stress scale is a standardized and reliable instrument used for data collection. The results indicated students’ susceptibility to academic stress was more in females than males. Moreover, different academic stress levels were reported for across various departments. The students need regular interval of checks of academic stress diagnosis and specialized on-campus counseling services to normalize effects of undergrads’ academic stress. The implications for future study require to focus on considering qualitative and quantitative methods to glean authentic data with a large sample size to make findings fit for generalizability.